1751 and Thereabout: A Quantitative and Comparative Approach to Notarial Records. Issue 3 (2022) - Lemercier, Claire; Trivellato, Francesca
Abstract: This article asks a simple question that nevertheless has broad implications for historians of premodern continental Europe: What did notaries do? It answers it by applying descriptive statistics, principal component analysis, and clustering techniques to the typological distribution of all deeds preserved in the notarial collections of six French and Italian cities—Paris, Toulouse, Mende, Turin, Florence, and Livorno—for the year 1751, as well as smaller datasets for other dates and locations. The results of this analysis are surprising. In spite of a high degree of consistency in the notarial profession and terminology (a trait that facilitates our comparisons), the notarial style of each city varied greatly. Variations within a single state were sometimes greater than those across state borders. Both supply and demand of notarial services differed from city to city. Overall, our conclusions are as important as the methodology that we adopt to reach them. Our aim is to offer a replicable analysis that puts quantitative methods in the service not only of the study of a source (notarial records) that is widespread across late medieval and early modern continental Europe and its overseas empires but also of a renewed comparative social history that does not shy away from the heterogeneity of primary sources.